2009
DOI: 10.1038/ajg.2009.66
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Capsule Endoscopy vs. EGD for the Evaluation of Portal Hypertension: A French Prospective Multicenter Comparative Study

Abstract: This large multicenter study confirms the safety and acceptable accuracy of ECE for the evaluation of esophageal varices. ECE might be proposed as an alternative to EGD for the screening of portal hypertension, especially in patients unable or unwilling to undergo EGD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 24 publications
2
35
1
Order By: Relevance
“…Also, as in the Choe et al [21] study, we found that concordance rates on grading esophageal varices were excellent at 95% (κ = 0.91). These results are better than those reported by using endoscopy capsule for detection of esophageal varices [7][8][9] . With regards to erosive esophagitis diagnosed at upper endoscopy, E.G.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Also, as in the Choe et al [21] study, we found that concordance rates on grading esophageal varices were excellent at 95% (κ = 0.91). These results are better than those reported by using endoscopy capsule for detection of esophageal varices [7][8][9] . With regards to erosive esophagitis diagnosed at upper endoscopy, E.G.…”
Section: Discussioncontrasting
confidence: 54%
“…Several studies have shown that ECE is safe and has an acceptable accuracy for the evaluation of esophageal varices and can be used as an alternative to EGD for the screening of portal hypertension, especially in patients unable or unwilling to undergo EGD [7,9] . Unsedated small-caliber transnasal esophagoscopy offers the possibility of efficient and accurate endoscopic assessment of the esophagus, with less cost and fewer risks compared with sedated upper endoscopy, and can be used as a method to screen for esophageal disease in a primary care population [11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant correlation has been found between capsule and standard endoscopy for the detection of varices. The sensitivity of capsule endoscopy ranged from 68% to 100% with a specificity ranging from 88% to 100% [49][50][51][52][53]. For the detection of large varices, the sensitivity was 78% with a specificity of 96% [52].…”
Section: Detection Of Varices and Prognostic Markers For Varicesmentioning
confidence: 99%
“…Among them, video capsule endoscopy appears to be a very promising tool for the detection of esophageal varices. Video capsule endoscopy has been compared to conventional upper endoscopy in several studies [49][50][51][52][53]. A significant correlation has been found between capsule and standard endoscopy for the detection of varices.…”
Section: Detection Of Varices and Prognostic Markers For Varicesmentioning
confidence: 99%